Caffeic Acid Induced Apoptosis in MG63 Osteosarcoma Cells Through Activation of Caspases - Sandra, Ferry; Sidharta, Meta Ariyani (Molecular and Cellular Biomedical Sciences, 2017)
Background:Â Caffeic acid has been reported that when it is combined withÂ all-transÂ retinoic acid, it can inhibit proliferation activity of SaOS-2 or OSA-01 cells. In addition, caffeic acid merely could reduce cell viability of SaOS-2 cells. However, there is not any study inÂ caffeicÂ acids possible effect to induce apoptosis in osteosarcoma cell.Materials and Methods:Â MG-63 cells were cultured in Dulbeccoâs Modified Eagle Medium containing 10% fetal bovine serum. Cells were treated with various concentrations of caffeic acid. ApoptosisÂ wereÂ analyzed with Sub-G1 assay and activation of caspase-8, -9, and -3 were analyzedÂ withÂ immunoblotting. Caffeic acid-induced percentage of apoptotic cells and cleaved-8, -9, -3 were then statistically analyzed.Results:Â Sub-G1 results showed that caffeic acid significantly induced apoptosis in MG-63 osteosarcoma cells in concentration dependent manner. Immunoblotting results showed that caffeic acid induced cleavage of caspase-8, -9 and -3. Cleaved-caspase-8 and -9 were increased at 1-hour treatment of caffeic acid, while cleaved-caspase 3 was increased markedly atÂ 6-hoursÂ treatment of caffeic acid.Conclusions:Â Caffeic acid induces apoptosis significantly in concentration dependent manner throughÂ caspase-dependentÂ intrinsic apoptotic pathway.Keywords:Â caffeic acid, osteosarcoma, MG-63, apoptosis, caspase